Motivation-based Human Needs and their Disclosure Prompts in Chris Cleave’s Little Bee - Asst. Prof. Hanan Abbas Hussein; Asst. Prof. Dr. Rana H. Al-Bahrani (International Journal on Humanities and Social Sciences, 2025)
The present work folds two qualitative objectives; the first focuses on investigating the multiplicity of motivation-based human needs in Little Bee. The second objective involves examining the linguistic forms adopted to disclose such needs. Consequently, the researchers are to adapt eclectically Alderfer’s Existence, Relatedness, and Growth Theory (1969) and Langacker’s theory of Domains (1987) together with his Active Zone Operation (1991). Such a study helps to embody the connectivity between the social and psychological aspects, and the way these two aspects are disclosed using particular linguistic The study has concluded that Bee needed Alderfer’s basic human needs: existence, relatedness, and growth. Besides, satisfying part of the existence sub-needs does not guarantee maintaining one’s existence. Moreover, Bee has used various linguistic styles to meet the existence sub-needs, such as: simple past tense, wish expressions, or a metaphorical language. Finally, cognitive linguistics has proven its effectiveness in addressing literary texts; any psychological changes will definitely be activated in the mind and ultimately in language.